PERENCANAAN TEBAL PERKERASAN LENTUR JALAN RAYA KALIBARU â€“ GLENMORE KABUPATEN BANYUWANGI ( PERBANDINGAN METODE BINAMARGA 1987 & 2013) - Hidayat, Muhammad Arif; Abadi, Taufan; Manggala, Adhitya Surya (HEXAGON, 2019)
Roads are infrastructure that play a very important role in traffic flow, so that during the road service period, efforts are made to avoid problems related to road damage. Road infrastructure which is burdened by high and repetitive traffic volumes will cause a decrease in road quality that can be seen from the condition of the road surface, both structurally and functionally damaged. This study aims to re-plan the thickness of the flexible pavement on the Kalibaru highway - Glenmore Banyuwangi Regency. In this study, to find out how thick the flexible pavement of the Kalibaru - Glenmore highway in Banyuwangi Regency for the next 20 years is in 2038. In this study the authors used the Binamarga Method 1987 and 2013. In this method we have to conduct LHR surveys on these roads and do CBR data retrieval. After the data data is collected, then we can determine the Index of Pavement Thickness of the road.Â  From the calculation results, it is known that the results of the pavement thickness with the Binamarga 1987 method are 4.5cm Lapen / Laston, 15cm Upper Foundation Layer, 10cm Bottom Foundation Layer. Whereas the thickness of road blocks with the method of Binamarga 2013 is WC air conditioner of 4cm, AC BC of 13.5cm, CTB of 15cm, LPA of Class A of 15cm.